APAKAH MORALITAS INDIVIDU MEMODERASI PENGARUH PARTISIPASI MASYARAKAT DAN KOMPETENSI APARATUR DESA TERHADAP AKUNTABILITAS PENGELOLAAN DANA DESA? (STUDI PADA DESA DI KOTA BANDA ACEH) - Nahwa, Firna; Batara, Gamal (Jurnal Ilmiah Mahasiswa Ekonomi Akuntansi, 2023)
This study intends to investigate the impact of community involvement, village apparatus competence, and individual morality on the accountability of village fund management. 136 respondents were obtained for the research, including village secretaries, and heads of financial affairs, and all of them were from 48 villages in 9 sub-districts in Banda Aceh City. From March to May 2023, a questionnaire was given to respondents to collect the necessary data. Using the SPSS version 25 program, multiple linear regression analysis and moderated regression analysis are the data analysis techniques performed. The findings indicated that community participation (X1), village apparatus competence (X2), and individual morality (Y) cannot moderate the influence of community participation, village apparatus competence, and village fund management accountability on village fund management accountability.